Epistemic Objectivity and the Virtues - Sankey, Howard (Filozofia Nauki, 2020)
The aim of this paper is to bring the resources of virtue epistemology to bear on the issue of the epistemic objectivity of science. A distinction is made between theoretical virtues, which may be possessed by scientific theories, and epistemic virtues, which may be exercised by individual scientists. A distinction is then made between ontological objectivity, objectivity of truth, and epistemic objectivity, the last being the principal focus of the paper. It is then noted that a role must be played by deliberative judgement in determining how to apply the theoretical virtues. It is suggested that such judgement may be virtuous in light of the exercise of the epistemic virtues. It is argued that the primary location of epistemic objectivity is the theoretical virtues, whereas the epistemic virtues of scientists play a subordinate role.